Selling reputation when going out of business - Hakenes, Hendrik,Peitz, Martin (Univ., Center for Economic Studies [u.a.], 2004)
Is the reputation of a firm tradeable when the previous owner has to retire even though ownership change is observable? We consider a competitive market in which a share of owners must retire in each period. New owners, observing only recent profits, bid for the firms on sale. Customers are concerned with the owners’ type, which reflects the quality of the good or service provided. When a customer observes an ownership change, he may have an incentive to switch to a different firm even if his past experience was good. However, we show that, in equilibrium, customers believe that also the new owner is of the good type. Hence reputation is tradeable, although ownership change is observable. In our model, reputation is an intangible asset, embodied in an attractive customer base. Firms owned by a good type sell at a premium.
Internetausg.: http://www.cesifo.de/ DocCIDL/cesifo1_wp1213.pdf
Keywords: Arbeitspapier; Graue Literatur; Übernahme; Unternehmensnachfolge; Firmenimage; Ärzte; Immaterielle Güter; Theorie